Second Hankel Determinant for Strongly Bi-Starlike of order α - Chow Li Yong; Aini Janteng; Suzeini Abd. Halim (Research India publications, 2018)
Let A denote the class of functions f (z) = z + ∞ n=2 anz n which are analytic in the open unit disc U = {z : |z| < 1}. Let S denote the class of all functions in A that are univalent in U. A function f ∈ A is said to be bi-univalent in U if both f and f −1 are univalent in U. Let denote the class of bi-univalent functions in U. In this paper, we obtained the upper bounds for the second Hankel functional |a2a4 − a2 3 | for strongly bi-starlike of order α